Allopolyploid speciation in primroses of the Auricula section (genus Primula, subgenus Auriculastrum) - MOSCO M. C; GAROFALO L; ARDUINO P; CIANCHI, Maria Rossella; BULLINI, Luciano (2007)
In the present study, we show that the hexaploid primroses (6x=66) of section Auricula arose from crosses between species of Dodecatheon (4x=44) and of Primula, section Cuneifolia (2x=22), that came into secondary contact in the Alps. Genetic studies at codominant nuclear markers (enzyme loci) indicate that the most likely parental species of the Auricula taxa were D. pulchellum, D. frigidum and P. cuneifolia. Among the alleles detected in Auricula species, 9 were found in a diploid population of P.cuneifolia from Siberia, 17 in allotetraploid D. pulchellum s.l./D. frigidum respectively from NW Canada and Alaska, whereas few were shared by both P .cuneifolia and Dodecatheon spp. Nine missing alleles were detected; their relative low frequency (about 1/4 of the total alleles) suggests that the Auricula section had a recent origin, during one of the last Ice Ages. We suggest that triploid P.cuneifolia x Dodecatheon spp. hybrids acquired sexuality by a chromosome doubling, allowing normal meiosis. Data from cpDNA indicate D.pulchellum s.l./D.frigidum as the maternal species of the Auricula complex. The putative parental species are now extinct from all Europe, possibly due to competitive exclusion by their allohexaploid derivatives, able to exploit a wide range of environments, from sea-level (i.e. P.palinuri) up to 3000m.